Rehabilitasi Sosial Komprehensif terhadap Lansia: Studi Kasus UPT Mulia Dharma di Kalimantan Barat, Indonesia - Kristina, Kristina; Alamri, Annisa Rizqa; Marini, Marini; Fiyani, Tri Octa; Listyaningrum, Indah; Ricarpan, Ogi Ricarpan; Arisdiyoto, Iving; Sinaga, Putri Meliani Clarancia (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2024)
Elderly rehabilitation is one of the programs made by the government to provide services to people who are 60 years and over but have welfare problems. This research aims to analyze the use of the UPT of the Elderly Rehabilitation Social Home and Rehabilitation of the Disabled Mulia Dharma as an effort to improve the welfare of the elderly. This research uses a qualitative method that takes a descriptive approach. The data taken for this study uses observation methods, in-depth interviews and documentation. From the research results of the UPT Elderly Rehabilitation Social Center and Rehabilitation of People with Disabilities Mulia Dharma has been said to be optimal because the services and facilities provided can improve the welfare of the elderly who live there.